(untitled) (Eurasian Research Bulletin, 2026)
This article discusses the use of interactive methods in educating students, not limited to traditional teaching methods, but to increase the quality of teaching and achieve high efficiency. For this, teachers must have the skills to use pedagogical technologies in their lessons, live and thereby express their identity in society, that is, mature as a person. At the current stage of education, the goal is to teach technology using pedagogical technologies.